1994
DOI: 10.1016/0035-9203(94)90475-8
|View full text |Cite
|
Sign up to set email alerts
|

Arteether administration in humans: preliminary studies of pharmacokinetics, safety and tolerance

Abstract: The recently developed artemisinin derivative arteether was administered by intramuscular injection to healthy male subjects in a single dose (n = 23) and a multiple dose study (n = 27). The drug was well tolerated. Clinical, neurological, electrocardiographic and biochemical monitoring did not reveal significant toxicity. Apart from some increase in eosinophil numbers, no haematological abnormality was seen. Preliminary pharmacokinetic data showed a long elimination half life of 25-72 h and marked accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Phase I studies of the drug in healthy adult volunteers in The Netherlands documented its tolerability, safety, and pharmacokinetics (Jonkman JHG and others, unpublished data). 10 Phase II studies in Thai adults with uncomplicated and severe malaria showed safety and efficacy when used over a five-day period with an initial loading dose (Peeters PAM and others, unpublished data). Subsequently, a Phase III, multicenter, open label, randomized comparative efficacy study was proposed in African children with cerebral malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Phase I studies of the drug in healthy adult volunteers in The Netherlands documented its tolerability, safety, and pharmacokinetics (Jonkman JHG and others, unpublished data). 10 Phase II studies in Thai adults with uncomplicated and severe malaria showed safety and efficacy when used over a five-day period with an initial loading dose (Peeters PAM and others, unpublished data). Subsequently, a Phase III, multicenter, open label, randomized comparative efficacy study was proposed in African children with cerebral malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic data demonstrated that accumulation of AE and AM was observed in the plasma of rats, 6 beagle dogs, 7 rhesus monkeys (Q. G. Li, unpublished data), and humans 8,9 following multiple intramuscular (im) injections. The rat data demonstrated that the accumulation of AE in plasma was due to a slow and prolonged absorption from the injection sites.…”
Section: Introductionmentioning
confidence: 99%
“…PK data from various animal studies have shown that AE and AM will accumulate in the plasma of rats (Li et al, 1999b), beagle dogs (Classen et al, 1999), rhesus monkeys (Li et al, 2007a), and humans (Kager et al, 1994) following multiple intramuscular injections. Data collected from rat studies showed that the accumulation of AE in the plasma is due to a slow and prolonged absorption from the injection sites.…”
Section: Cause Of Am and Ae Accumulation After Intramuscular Injectionmentioning
confidence: 99%
“…The intramuscular administration of AM and AE was associated with slow absorption because the drugs were dissolved in sesame oil or peanut oil that, when injected, formed a depot from which the drug was slowly released (Kager et al, 1994: Li et al, 2004. The slow elimination of AE was recently demonstrated in a rat study, which also found significant accumulation of AE in the plasma from injection sites (Li et al, 1999b).…”
Section: Cause Of Am and Ae Accumulation After Intramuscular Injectionmentioning
confidence: 99%